Pengaruh Strategi Think Pair Share (Tps) Dan Two Stay Two Stray (Ts-Ts) Terhadap Hasil Belajar Matematika Ditinjau Dari Motivasi Belajar Siswa Kelas Viii Di Smp Negeri 2 Kartasura Tahun 2015/2016 - Isma Wanti, Nanik, Drs. Slamet H. W, M.Pd (2016)
The purpose of this study to understanding : (1) the effect of learning strategies Think Pair Share and Two Stay Two Stray on learning outcomes in mathematics; (2) The influence between students' motivation to learning outcome in mathematic; (3) The interaction between learning strategy and learning motivation of students toward mathematics learning outcomes. This study is a quantitative research. The design of the study is quasi-experimental design. The research sample was taken two classes. The population of the research was all students of class VIII SMP Negeri 2 Kartasura the academic year 2015/2016. The technique used cluster sampling is random sampling. Data collection techniques in this study using the test, a questionnaire and documentation. Technique of analysis data used two-way analysis of variance with different cells. The results of the data analysis with a significance level of 0.5%, namely: (1) there was an effect of learning strategies Think Pair Share and Two Stay Two Stray towards mathematics learning outcomes, with F_A = 4.459; (2) There is an effect between students' motivation to learn math results, with F_B = 14.657; (3) There is no interaction between the learning strategies with students' motivation to mathematic learning outcomes, withF_AB = 0.511.